"No one speaks Korean at school!": Ideological discourses on languages in a Korean family. Issue 1 (2nd January 2016) - Song, Kwangok
ABSTRACT: This study examined how a Korean family with temporary immigrant status in the United States employed ideological discourses on languages to make sense of their experiences. The parents initially accepted but later rejected ideologies on children's learning of English. English-as-a-legitimate-language ideology in the United States and English-as-linguistic-capital ideology challenged the parents' efforts to teach their children Korean. The focal child showed a sign of internalizing the language ideologies dominant at school. This study urges educators to pay attention to immigrant parents' perspectives on their children's language experiences and the impact of English-only ideology on the experiences of transnational families and children.